Developmental Supportive Care for Preterm Infants in Neonatal Intensive Care Units - Shrestha, Tumla (Journal of Nursing Education of Nepal, 2022)
Survival of preterm infants (PTIs) is increasing with the availability of neonatal intensive care, advanced technologies and equipment. Nonetheless, they are vulnerable to developmental impairment. They require special care in neonatal intensive care units (NICU) involving their parents for survival with development. Therefore, this article was prepared to enhance awareness about the need and components of those care among nurses working in neonatal care units (NCUs). A review of the relevant literature showed that interventions for supporting the development of the infant include minimizing the environmental stressors in NICU. Some effective Developmental Supportive Care (DSC) interventions are skin-to-skin contact (SSC) or kangaroo mother care (KMC), breast milk feeding, sleep protection, positioning and handling, supportive sensory environment, protecting skin, stress and pain management, and minimizing infant-parent separation